Future of Asia's Finance : How Can it Meet Challenges of Demographic Change and Infrastructure Needs? - Ding, Ding (IMF Working Papers; Working Paper ;, 2014)
There is a role for Asia's financial sector to play to address the challenges associated with the region's changing demographics and infrastructure investment needs. Enhancing financial innovation and integration in the region could facilitate intra-regional financial flows and mobilize resources from the aging savers in industrialized Asia to finance infrastructure investment in emerging Asia. Strengthening the financial ties within the region as well as with the global financial markets alongside appropriate prudential frameworks could also help diversify sources of financing and reduce the cost of funding in emerging Asia. Finally, financial deepening could help ease the potential overheating from scaling up infrastructure investment and hence achieve a more balanced growth in the region.